Paradigms in the eye of the beholder: Aristotle, Ptolemy and Copernicus - Taub, Liba (Journal of physics. Conference series, 2024)
Accounts of the history of physics sometimes describe major paradigm shifts followed by decades and even centuries of working through the consequences of the dominating paradigm. Some examples that are often pointed to as paradigm shifts are the Copernican revolution overtaking the millennium-old Ptolemaic system of astronomy and Newton’s mechanics replacing the ancient Aristotelian system. However, when thinking about ‘paradigm shifts’, there may be various different candidates that can be identified as possible ‘paradigms’ retrospectively. Thus it may be the case that paradigms are in the eye of the beholder.